Cost Behavior: Mapping and Systemic Analysis of International Publications - Fernando Richartz; Altair Borgert; Sandra Rolin Ensslin (Revista Sociedade, Contabilidade e Gestão, 2014)
This article has as objective mapping of scientific researches into costs behavior to identify its current scenario. The research on database provided a selection of relevant bibliographic portfolio, which had as a result 29 articles according to the research criteria defined in the study. From those, the articles from Anderson, Banker e Janakiraman (2003) were highlighted. Furthermore, Banker is considered to be the main author about costs behavior, its importance is noticed not only in the portfolio itself, but also, in its references. The most important periodic, either for its impact, or related to its number of articles publicized, is The Accounting Review. Finally, from the relationship between the most important articles about bibliometric analysis, featuring systemic analysis, the conclusion is that an important article about cost behavior has a quantitative approach (with the use of robust regression), recognize the existence of Sticky Costs (no matter which approach is in use), makes use of a variety of explanations (internal & external) and add some variable or information for scientific evolution of the subject.